Implementation of Multimedia Learning Applications to Increase Understanding of Kirana Hati Bunda Tamiajeng Special School Students - Endah Asmawati; Heru Arwoko; Aniva Kartika (Indonesian Journal of Cultural and Community Development, 2023)
Kirana Hati Bunda Special School (SLB) is the only special school in Trawas District. This school has 19 students with special needs who come from several villages in Trawas District. The village fully bears operational costs, so the development of SLB has been quite slow. Due to limited funds, teachers are often unable to attend training to add skills and knowledge to the teaching and learning process. Teachers still have difficulties in compiling learning programs according to the different needs of students, innovating, and being creative in developing new learning media. Therefore, this program will provide training and assistance in planning, implementing, and evaluating learning for SLB Kirana Hati Bunda students. In addition, to meet the needs of teaching aids, learning applications will be made, training on application use and assistance in using multimedia learning applications with hand gesture recognition. Based on student learning results, it was found that the multimedia hand gesture recognition learning application made students more enthusiastic in learning, did not get bored of repeating exercises and the results were better when learning was done repeatedly. From two practice sessions on the same material there was a significant increase in scores